2015
DOI: 10.1016/j.acalib.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Copyright Instruction in LIS Programs: Report of a Survey of Standards in the U.S.A.

Abstract: This article will detail the results of a survey distributed within the United States of America to professionals working in academic, public, school/media, and special libraries that asked respondents to rate their daily copyright and intellectual property knowledge needs vs. their actual knowledge and education in this area. The results were then compared with an analysis of course content in current ALA accredited LIS programs in the U.S. gathered from online course descriptions to determine whether there i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 11 publications
(3 reference statements)
0
23
0
Order By: Relevance
“…investigated the copyright/IP instruction in ALA-accredited LIS programs in the United States against practitioner needs of copyright/IP knowledge by comparing LIS course descriptions with survey data from practitioners. They concluded that although recent graduates of LIS programs in the United States are more likely to have had instruction on copyright/IP issues, this instruction is not widespread enough, nor in depth enough to prepare LIS program graduates for the current demands of the workplace (Schmidt and English, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…investigated the copyright/IP instruction in ALA-accredited LIS programs in the United States against practitioner needs of copyright/IP knowledge by comparing LIS course descriptions with survey data from practitioners. They concluded that although recent graduates of LIS programs in the United States are more likely to have had instruction on copyright/IP issues, this instruction is not widespread enough, nor in depth enough to prepare LIS program graduates for the current demands of the workplace (Schmidt and English, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers are also interested in analysing undergraduate student performance (Soria et al 2014) and how they integrate into university life, including their experiences of anxiety (Sinnasamy and Karim 2014). While few papers discuss teaching methods in combination with undergraduate education, researchers who examine the topic curriculum also assess the effectiveness of teaching methodologies (e.g., Schmidt and English 2015). Researchers are interested in how to integrate information literacy in the educational curriculum (Moselen and Wang 2014;Salmerón et al 2016) and the connections between curriculum and real-world experience in teaching information literacy (Young and Maley 2018).…”
Section: Mann-kendall and Sen's Slope Analysismentioning
confidence: 99%
“…Others looked at the instructional roles of librarians on college campuses (Zerkee, 2016). But only a handful tackled the curriculum issues in LIS programs that prepare future librarians (Gathegi & Burke, 2008;Cross & Edwards, 2011;Dryden, 2011;Schmidt & English, 2015). Even then these studies do course-level analysis focusing on the presence or lack of copyright and intellectual property (IP) courses in the curricula.…”
Section: Copyright Education and Lis Curriculamentioning
confidence: 99%
“…The Schmidt and English (2015) study looking at copyright education in LIS programs is the most recent known to the authors. Schmidt and English (2015) examined 51 ALA-accredited LIS programs for copyright courses, using the course catalogs and course descriptions as sources of data. While the Schmidt and English (2015) study was an important addition to the literature, their analysis of copyright courses was cursory at best.…”
Section: Copyright Education and Lis Curriculamentioning
confidence: 99%